The Celts - Chapman, M. author. aut Link
XV, 342 p.
Keywords: The Celts are commonly considered to be one of the great peoples of Europe, with continuous racial, cultural and linguistic genealogy from the Iron Age to the modern-day 'Celtic fringe'. This book shows, in contrast, that the Celts, as they have been known and understood over two thousand years, are simply the 'other' of the dominant cultural and political traditions of Europe. It is this continuous 'otherness' which lends them apparent continuity and substance.